2013
DOI: 10.1371/journal.pone.0058412
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants in the Adiponectin Gene with Metabolic Syndrome: A Case-Control Study and a Systematic Meta-Analysis in the Chinese Population

Abstract: BackgroundThe prevalence of metabolic syndrome has been rising worldwide, including in China, but knowledge on specific genetic determinants of metabolic syndrome is very limited. A number of studies have reported that polymorphisms in the ADIPOQ gene are associated with metabolic syndrome in Chinese Han populations. However, data is still conflicting. The objective of this study was to examine the associations of the adiponectin genetic variants with metabolic syndrome by a case-control study and meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 77 publications
(68 reference statements)
2
25
1
Order By: Relevance
“…This is intriguing, as evidence suggests that individuals homozygous for the G allele are at greater metabolic risk than T-allele carriers. For example, a recent meta-analysis of Chinese Han populations reported a greater G allele frequency in individuals with MetS [37]. Further, individuals homozygous for the GG genotype showed impaired glucose tolerance in Spanish subjects [35].…”
Section: Discussionmentioning
confidence: 99%
“…This is intriguing, as evidence suggests that individuals homozygous for the G allele are at greater metabolic risk than T-allele carriers. For example, a recent meta-analysis of Chinese Han populations reported a greater G allele frequency in individuals with MetS [37]. Further, individuals homozygous for the GG genotype showed impaired glucose tolerance in Spanish subjects [35].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that +45G allele may confer a protective effect against metabolic disease and CVD in the Taiwanese population. On the other hand, in other regions of China, meta-analysis studies have reported that the G allele does not consistently show protective effects on metabolic syndrome [31], T2D [22], or CVD [32]. These contrasting results in different regions of Chinese might be explained by regional variations and different study methods including diagnostic criteria, sample size, and study design.…”
Section: Of 24mentioning
confidence: 95%
“…Nonetheless, Li et al [50] conducted a meta-analysis of Chinese Han population and found that ADIPOQ T45G may be a susceptible allele of T2D. Gao et al [51] also reported that ADIPOQ T45G is strongly associated with metabolic syndrome in Chinese Han population. FBG is an important T2D-related trait.…”
Section: Discussionmentioning
confidence: 99%